STRATEGI IMPLEMENTASI TANGGUNG JAWAB SOSIAL LINGKUNGAN DALAM PERUSAHAAN: DAMPAK DAN TANTANGAN - Nuriyatman, Eko; Fitria, Fitria; Naili Hidayah, Lili; Fatimah, Siti; Irawan, Agus (Faculty of Law, Universitas Pasundan, 2024)
Environmental Social Responsibility is regulated in Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies as part of Corporate Social Responsibility, which encourages companies to act ethically and contribute to improving the quality of life of the community. This study uses a normative legal method to analyze legal norms related to Environmental Social Responsibility and Corporate Social Responsibility and their application in practice. The problems discussed in this scientific article are related to the review of the implementation of environmental social responsibility by State-Owned Enterprises. The discussion includes strategies for implementing Environmental Social Responsibility which include analysis of community needs, stakeholder involvement, and allocation of sufficient resources. Evaluation of the impact of Environmental Social Responsibility is carried out through sustainability reports and the use of Key Performance Indicators, with support from international standards such as ISO 26000 and the Global Reporting Initiative. In conclusion, the effective implementation of Environmental Social Responsibility requires a comprehensive and collaborative approach, where companies must align Corporate Social Responsibility activities with the objectives of the Sustainable Development Goals. Advice for companies is to increase transparency and accountability in reporting Environmental Social Responsibility and integrate feedback from the community for more relevant and impactful programs. Thus, it is hoped that Environmental Social Responsibility will not only provide benefits for the company, but also for the community and the environment in a sustainable manner.